PROJECTION AND DEVELOPING OF WEB-SITES OF THE FACULTIES OF MELITOPOL’ STATE TEACHERS TRAINING UNIVERSITY NAMED AFTER BOHDAN KHMEL’NITSKIY (Journal of Information Technologies in Education (ITE), 2011)
The article describes experience of projection and developing of the system of web-sites of Melitopol’ State teachers training University named after Bohdan Khmel’nitskiy’s faculties: stages of projecting, generalrequirements and demands to functioning and design, structure, principles of content building of the developed information sources.
Keywords: projecting; virtual university; web-site of a faculty